Một số yếu tố ảnh hưởng đến quá trình cố định đoạn ADN bằng phương pháp điện hoá - Tâm, Phương Đình (Vietnam Journal of Chemistry, 2015)
Immobilization of DNA sequence onto sensor surface is one of factors impact sensitivity, response time and lifetime of biosensor. In this work, the DNA probe and polypyrrole (Ppy) was directly co-immobilized on sensor surface by cyclic voltammetry method. The influence factors were investigated such as potential, scanning rate, DNA probe concentration. The obtained results showed that the potential was used to attach DNA probe from –1.2 V to +1.2 V. The DNA probes concentration and scanning rate were 0.05 µM and 100 mV/s, respectively. Additionally, the influence study of media composition showed that signal response of DNA probe/Ppy co-immobilized sensor was better than that of ADN probe/APTES and ADN probe/ZnO nanowire immobilized sensors.